PENERAPAN INHALASI MINYAK KAYU PUTIH TERHADAP BERSIHAN JALAN NAFAS TIDAK EFEKTIF PADA BALITA ISPA - Ananda Istikomah; P. Sulistyowati; Rahaju Ningtyas (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
A child is someone special in his developmental activities. Among these developments are physiological such as eating and drinking, excretory exercise, sleep and rest. ARI is an acute respiratory infection that can last up to 14 days and is caused by a virus or bacteria. The illness begins with a fever with one or more symptoms including, runny nose, dry cough, phlegm, sore throat to swallow. Ineffective airway clearance is a core problem that often occurs in children with ARI. This scientific writing used is a type of case study with a descriptive approach, the method of collecting data is in the format of assessment, format of child development, interviews and observation sheets. The inclusion criteria were children diagnosed with mild or moderate ISPA, children aged 4-5 years, parents of patients who were able to communicate well and were cooperative, parents of patients who were willing to be respondents by signing an informed consent. Exclusion criteria were children who had ARI with a severe diagnosis, uncooperative clients or parents. During the 3 day meeting, nursing care was carried out by inhaling effective eucalyptus oil vapor in children with ARI, obtained data on decreased secretion production, rhonchi, cough, dyspnea. The application of eucalyptus oil vapor inhalation is effective in children under five suffering from ARI with the main problem being ineffective airway clearance.